HINDUISM IN MODERN INDONESIA A minority religion between local, national, and global interests - Martin Ramstedt (RoutledgeCurzon, 2004)
This volume has mainly grown out of the initial paper presentations and discussions at the International IIAS-Seminar on ‘Hinduism’ in Modern Indonesia, which I convened on 16–17 September 1999 in Leiden, the Netherlands. At that time, I was a European Science Foundation (ESF) research fellow at the International Institute for Asian Studies (IIAS). Due to the generous arrangements made by the IIAS and thanks to additional funding from the Dutch Organization for Scientific Research (Nederlandse Organisatie voor Wetenschappelijk Onderzoek, NWO), all the paper presenters and discussants were especially invited. We enjoyed two tightly scheduled days full of intense discussions both inside and outside the place of convention. These discussions, from which most of the contributions in this book have profited, would not have been so intense without the participation of the five discussants. I would, therefore, like to extend my thanks to Dr Nico Kaptein (Indonesian- Netherlands Cooperation in Islamic Studies, INIS, Leiden, the Netherlands), Drs (Doctorandus) Sirjo Koolhof (Koninklijk Instituut voor Taal-, Land- en Volkenkunde, KITLV/ Royal Institute for Anthropology and Linguistics, Leiden, the Netherlands), Prof. Dr Peter Pink (Malaiischer Apparat, Orientalisches Seminar, Universität zu Köln/Malay Studies, Department for Oriental Studies, Cologne University, Cologne, Germany), Prof. Dr Henk Schulte Nordholt (Faculteit der historische en kunstwetenschappen, Erasmus Universiteit/Faculty of Historical Sciences and the Arts, Erasmus University, Rotterdam, the Netherlands), and Prof. Dr Peter van der Veer (Onderzoekschool Godsdienst en Maatschappij, Universiteit van Amsterdam/Research School Religion and Society, Amsterdam University, the Netherlands).